Performance of the Direct Sequence Spread Spectrum Underwater Acoustic Communication System with Differential Detection in Strong Multipath Propagation Conditions - Jan H. SCHMIDT; Iwona KOCHAŃSKA; Aleksander M. SCHMIDT (Archives of Acoustics)
The underwater acoustic communication (UAC) operating in very shallow-water should ensure reliable transmission in conditions of strong multipath propagation, significantly disturbing the received signal. One of the techniques to achieve this goal is the direct sequence spread spectrum (DSSS) technique, which consists in binary phase shift keying (BPSK) according to a pseudo-random spreading sequence. This paper describes the DSSS data transmission tests in the simulation and experimental environment, using different types of pseudo-noise sequences: m-sequences and Kasami codes of the order 6 and 8. The transmitted signals are of different bandwidth and the detection at the receiver side was performed using two detection methods: non-differential and differential. The performed experiments allowed to draw important conclusions for the designing of a physical layer of the shallow-water UAC system. Both, m-sequences and Kasami codes allow to achieve a similar bit error rate, which at best was less than 10−3. At the same time, the 6th order sequences are not long enough to achieve an acceptable BER under strong multipath conditions. In the case of transmission of wideband signals the differential detection algorithm allows to achieve a significantly better BER (less than 10−2) than nondifferential one (BER not less than 10−1). In the case of narrowband signals the simulation tests have shown that the non-differential algorithm gives a better BER, but experimental tests under conditions of strong multipath propagation did not confirm it. The differential algorithm allowed to achieve a BER less than 10−2 in experimental tests, while the second algorithm allowed to obtain, at best, a BER less than 10−1. In addition, two indicators have been proposed for a rough assessment which of the detection algorithms under current propagation conditions in the channel will allow to obtain a better BER.